A multispecies turbulence model for the mixing and de-mixing of miscible fluids. Issue 12 (2nd December 2021) - Braun, N. O.; Gore, R. A.
Abstract : A de-mix capable model for turbulence in compressible, variable density flows is proposed. The model is based on the Besnard-Harlow-Rauenzahn (BHR) family of models (Besnard D, Harlow F, Rauenzahn R, et al. Turbulence transport equations for variable-density turbulence and their relationship to two-field models. NM (United States): Los Alamos National Laboratory; 1992 (Technical Report LA-12303-MS), but is extended to track the evolution of the turbulent fluxes and fluctuations in the material mass fractions for each species present. The new evolution equations are introduced without requiring additional closures or new empirically tuned coefficients relative to previous BHR models, and are shown to improve the model's ability to reproduce the behaviour of simulations containing mixing layers that are constrained by a stabilising force. The model is tested in a range of canonical flows including Rayleigh-Taylor driven, shock driven, and shear driven turbulence, and is shown to produce reasonable agreement with simulations and experiments in these scenarios.